Online Shopping and Buying Behavior of College Students in Kathmandu - Lama, Padam Bahadur (Interdisciplinary Journal of Management and Social Sciences, 2021)
This study examines the association and impact of online shopping on buying behavior of college students in Kathmandu. The delivery guarantee (DG), product quality (PQ),service information quality (SIQ), and website factor (WF) are independent variables. The dependent variable is buying behavior of college students (BBCS). The research is based on primary data collected from college students in Kathmandu. The cross-sectional data is mainly gathered from college students as a user of online shopping. Structured questionnaire of total 500distributed and received 115 (23 percent) useful data from respondents. The regression models are estimated for assessing the significance and impact of delivery guarantee, product quality, service information quality, and website factor on buying behavior of college students.The study shows that delivery guarantee is positively associated with buying behavior of college students. It reveals that the higher the delivery guarantee, higher would-be buying behavior of college students. The product quality is positively related with buying behavior of students but found insignificant. However, the service information quality is positively related with buying behavior of college students. It shows that higher the service information quality, higher would be the buying behavior of college students. Similarly, the website factor is found positively associated with buying behavior of college students. It depicts that the supportive website factor increases the buying behavior of college students.